Safety and efficacy of tirofiban after intravenous thrombolysis with urokinase in patients with acute ischemic stroke - Qu, Dian; Liu, Huanhuan; Wei, Zhongming; Cheng, Yao; Fei, Yutong; Xu, Jinghan; Lv, Xiuyu; Li, Wendi (Frontiers in Neurology, 2025)
IntroductionTirofiban combined with alteplase thrombolysis or endovascular therapy has been proven to improve the prognosis of patients with acute ischemic stroke (AIS). Some patients, due to the extended time window beyond 4 h and economic considerations, opt for urokinase thrombolysis instead of alteplase thrombolysis in China. However, there is currently limited research on the use of urokinase thrombolysis bridged with tirofiban.MethodsWe employed propensity score match to pair 80 sets of patients from a total of 196 individuals who underwent urokinase thrombolysis for acute ischemic stroke. The study analyzed the 14-day National Institutes of Health Stroke Scale (NIHSS), 90-day modified Rankin Scale (mRS), bleeding events, and compared the odds ratio (OR) of patients with mRS scores of 0–2 within the subgroups.ResultsThe results show that the NIHSS at 14 days of the tirofiban group was significantly lower than that of the dual antiplatelet group. No significant difference was found in the proportion of patients with mRS score 0–2. The odds ratios were slightly different in subgroups classified with or without previous stroke and hypertension.DiscussionIt was confirmed that the tirofiban might be safe in AIS patients received tirofiban after urokinase thrombolysis and could improve short-term neurological function.